STUDI TENTANG SIMBOL NILAI DAN NORMA SOSIAL DI MASYARAKAT DESA PERCUT - Ginting, Anisa Nur Baidah; Sembiring, Dinda Menda Pepayosa Br; Silitonga, Emi Sofya Pratiwi; Nst, Fulka Al Uways; Hasbianda, Rhasya Adhira Putri; Silaban, Sherina Betharia; Anifah, Anifah (Jurnal Manajemen Pendidikan, 2025)
Changes in social interaction patterns that occur due to globalization shift the way people internalize cultural values that have been passed down from generation to generation. This research examines the role of cultural symbols in the formation of social values and norms in the Percut Village community. A qualitative approach was used with in-depth interview methods, participatory observation, and documentation studies to explore the meaning and application of cultural symbols in everyday life. Data were collected through direct interaction with key informants in the village environment to understand how symbols such as tepak sirih and bale adat contribute to internalizing the values of kinship, gotong royong, and religiosity, thus helping to maintain social order. The results show that, amidst the influence of modernization, there is a shift in traditional values that affect patterns of social interaction. The findings emphasize the importance of preserving cultural symbols as an effort to maintain the identity and cohesion of local communities in an era of changing times. The contribution of this research is expected to enrich the study of cultural sociology and become the basis for developing adaptive strategies in preserving local traditions.